A solution technique to an economic dispatch problem - Pramuan Kongsakorn (1977)
This text presents a solution procedure to include the voltage controlled buses and the boundary problems of power system in an economic dispatching problem. The method uses a discrete checking of the violations and rescheduling the boundary problems. The method of Lagrangian multipliers and the Newton-Raphson technique of the optimal scheduling problem are developed, and the method is illustrated on a small network example. Rigorous formulation and inclusion of the inequality constraints assure that the solution always represents an optimum dispatch and the system operates within the boundary conditions.